Temperature-Dependent Reproductive Success of Stickleback Lateral Plate Morphs: Implications for Population Polymorphism and Range Shifts Under Ocean Warming - Wanzenböck, Sylvia; Fuxjäger, Lukas; Ringler, Eva; Ahnelt, Harald; Shama, Lisa N. S. (Frontiers in Marine Science, 2022)
Changing environments associated with rapid climate change can shape direct measures of fitness such as reproductive success by altering mating behaviour, fecundity and offspring development. Using a polymorphic oceanic population of threespine stickleback (Gasterosteus aculeatus), we investigated whether a 4°C increase in sea surface temperature influenced clutch siring success, reproductive output, and offspring growth among lateral plate morphs. Since low plated morphs are thought to have a selective advantage in warmer environments, we predicted that low plated males should have higher clutch siring success in +4°C environments, and that thermal plasticity of traits (e.g. egg size, offspring growth) should reflect different trait optima in different environments among plate morphs. Parentage analysis of egg clutches revealed temperature-specific clutch siring success, in that low plated males sired more clutches in +4°C environments and completely plated males sired more clutches at ambient (seasonal) temperature. Both completely and low plated females laid larger eggs when acclimated to +4°C, but only completely plated females had smaller clutches at +4°C. Offspring of low and partially plated females grew much less at +4°C compared to those of completely plated females. Taken together, our results demonstrate that ocean warming could impact reproductive success at various levels, with differential effects depending on phenotype, in this case, lateral plate morph. Some traits (clutch siring success, egg size) showed better performance for low plated fish at +4°C, whereas others (e.g. growth) did not. Higher clutch siring success of low plated males at elevated temperature might indicate a future shift in plate morph composition for polymorphic stickleback populations, with potential implications for colonisation ability during range shifts under climate change.